2017
DOI: 10.1049/iet-its.2016.0223
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled H control of automated vehicular platoons with complex interaction topologies

Abstract: The platooning of automated vehicles has potential to significantly benefit road traffic, while its robust performance is less investigated especially considering increasing complexity of interaction topologies. This study presents a decoupled H ∞ control method for automated vehicular platoon to comprehensively compromise multiple performances. The platoon control system is first decomposed into an uncertain part and a diagonal nominal system through the linear transformation, which is motivated by the eigenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…From 16, it is found that the states of different AVs are coupled together by the information connections. To model various connection topologies among AVs in a consistent way, the graph theory is used to describe it as  =  +  ∈ ℝ N×N [14,15].  describes the connection between followers and is defined as And  represents the directional connection from leader to followers:…”
Section: Sliding Dynamics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From 16, it is found that the states of different AVs are coupled together by the information connections. To model various connection topologies among AVs in a consistent way, the graph theory is used to describe it as  =  +  ∈ ℝ N×N [14,15].  describes the connection between followers and is defined as And  represents the directional connection from leader to followers:…”
Section: Sliding Dynamics Analysismentioning
confidence: 99%
“…To deal with such uncertainties, Gao et al [14] further presented a robust control method for heterogeneous formations. This synthesis method has been extended to general, but eigenvalue decomposition known topologies in [15] and even with communication delays [16].…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous feedback structure has advantages over homogeneous one in some performances such as string stability, but only special topologies such as biodirectional can be dealt with [15]. To provide a synthesis strategy applicable for a variety of topologies and simplify the theoretical analysis, the identical state feedback control logic is used here [18,20,33]:…”
Section: Distributed State Feedbackmentioning
confidence: 99%
“…From (18), it can be found that the closed dynamics of platoon is influenced by both the state feedback and interaction topology. If the interaction topology is determined in advance and holds during running, many control theories can be used [15][16][17][18][19][20]. Unfortunately, both the dimension and structure of the topological matrix are uncertain in a real environment, which poses a great challenge to synthesize and analyze the platoon control system.…”
Section: Synthesis Of Distributed H ∞ Controllermentioning
confidence: 99%
See 1 more Smart Citation